Anomalous Recognition of Sirri Marriage through the Status of 'Unrecorded Marriage' in Permendagri No. 108/2019 - waton rosyit, achmad nasrul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The Ministry of Domestic Affairs Regulation No. 108 of 2019, which recognizes the status of "unregistered marriage" in population documents, has sparked serious debate about legal consistency and the validity of public policy in Indonesia. This study aims to analyze the conflict between this regulation and Law No. 1 of 1974 on Marriage and Law No. 23 of 2006 on Population Administration, as well as to evaluate the social and legal impact of giving administrative recognition to relationships that are not legally valid. This research uses a qualitative normative approach through literature study and legal document analysis, applying deductive reasoning and theories of legal hierarchy and social legitimacy. The findings show that Permendagri No. 108/2019 creates legal ambiguity and weakens legal certainty and public trust by allowing administrative status without proper legal basis. This study expands the discourse on family law dualism by critically examining administrative legitimacy without substantive legality, and promotes the synchronization of regulations based on legal and social principles. The main contribution of this study is to highlight the urgent need to synchronize regulations and reform marriage registration policy using an integrative approach that combines legal norms, social values, and access to justice. In conclusion, marriage registration policy must be redesigned to balance legal formalities with social legitimacy, ensuring better legal protection for families and stronger public trust in the law.